2015
DOI: 10.1105/tpc.114.135103
|View full text |Cite
|
Sign up to set email alerts
|

Functional Evolution of Phosphatidylethanolamine Binding Proteins in Soybean and Arabidopsis

Abstract: Gene duplication provides resources for novel gene functions. Identification of the amino acids responsible for functional conservation and divergence of duplicated genes will strengthen our understanding of their evolutionary course. Here, we conducted a systemic functional investigation of phosphatidylethanolamine binding proteins (PEBPs) in soybean (Glycine max) and Arabidopsis thaliana. Our results demonstrated that after the ancestral duplication, the lineage of the common ancestor of the FLOWERING LOCUS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
118
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(124 citation statements)
references
References 62 publications
5
118
0
1
Order By: Relevance
“…To determine the subcellular localization of the GmFT2b protein in planta , we fused the GmFT2b coding region with the gene for green fluorescent protein (GFP) under the control of the constitutive cauliflower mosaic virus (CaMV) 35S promoter and transfected the resulting p35S::GmFT2b‐GFP plasmid into onion epidermal cells. Confocal microscopy showed that the GmFT2b protein is expressed in the cytoplasm and nucleus, with a stronger signal in the nucleus (Figure S2), similar to the cellular localization of the other functional phosphatidylethanolamine binding proteins in soybean (Wang et al, ).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…To determine the subcellular localization of the GmFT2b protein in planta , we fused the GmFT2b coding region with the gene for green fluorescent protein (GFP) under the control of the constitutive cauliflower mosaic virus (CaMV) 35S promoter and transfected the resulting p35S::GmFT2b‐GFP plasmid into onion epidermal cells. Confocal microscopy showed that the GmFT2b protein is expressed in the cytoplasm and nucleus, with a stronger signal in the nucleus (Figure S2), similar to the cellular localization of the other functional phosphatidylethanolamine binding proteins in soybean (Wang et al, ).…”
Section: Resultssupporting
confidence: 69%
“…Soybean is a diploid species that evolved from an ancient tetraploid, and its genome has undergone homologous chromosomal recombination and reassortment of the entire genome during its long evolutionary history (Wang et al, ). At present, it has been shown that the soybean genome encodes at least ten members of the GmFT gene family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S2). Confocal microscopy observations suggested that the GmFT1a‐GFP fusion protein was located in the nucleus and in the cytoplasm (Figs c, S2), which is consistent with the subcellular localization of the other functional PEBPs in soybean (Wang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Duplicated genes can also be retained without functional changes to maintain their dosage balance (Birchler et al ., ; Veitia et al ., ; Birchler and Veitia, ). Some of these hypotheses above are supported by recent observations from soybean (Tian et al ., ; Du et al ., ; Wang et al ., ), but how genetic pathways or networks underlying a particular plant trait were modified following WGD have not been experimentally characterized.…”
Section: Introductionmentioning
confidence: 99%